The future of water in a desert river basin facing climate change and competing demands: A holistic approach to water sustainability in arid and semi-arid regions - Hargrove, H.L.; Granados-Olivas, Alfredo; Heyman, Joseph M.; Mayer, Alex; Mirchi, Ali; Ganjegunte, G.; Gutzler, David; Pennington, Deana D.; Ward, Frank A.; Garnica Chavira, Luis A.; Sheng, Shuping; Kumar, Subhash; et al. (2023)
Study region: The Middle Rio Grande (MRG), defined by the portion of the basin from Elephant Butte Reservoir in New Mexico to the confluence with the Rio Conchos in Far West Texas, U.S.A. and Northern Chihuahua, Mexico. Study focus: The future of water for the MRG and many other arid and semi-arid regions of the world is challenged by a changing climate, agricultural intensification, growing urban pop ulations, and a segmented governance system in a transboundary setting. The core question for such settings is: how can water be managed so that competing agricultural, urban, and envi ronmental sectors can realize a sustainable future? We synthesize results from interdisciplinary research aimed at “water futures”, considering possible, probable, and preferable outcomes from the known drivers of change in the MRG in a stakeholder participatory mode. We accomplished this by developing and evaluating scenarios using a suite of scientifically rigorous computer models, melded with the input from diverse stakeholders. New hydrological insights for the region: Under likely scenarios without significant interventions, relatively cheap and easy to access water will be depleted in about 40 years. Interventions to mitigate this outcome will be very costly. A new approach is called for based on “adaptive cooperation” among sectors and across jurisdictions along four important themes: information sharing, water conservation, greater development and use of alternative water sources, and new limits to water allocation/withdrawals coupled with more flexibility in uses.